Online Game and Childrens’s Language Behavior - Ahmad Munawir (Institut Agama Islam Negeri Palopo, 2019)
AbstractThis study examines the dangers of online games on children's language behavior. This research uses a qualitative approach with descriptive type. The data collection method uses observation by describing the results of video observations that show the interaction of children while playing online games. The online game that was studied was Playerunknown’s Battlegrounds (PUBG). The data obtained are then analyzed interactively by means of reduction, presentation, and drawing conclusions. The results showed that when playing online games children absorb a lot of abusive / negative language so that the language behavior becomes distorted. Words or terms that are often used by children such as dogs, idiots (monks), monkeys, bencong (sissy), dogs, idiots / idiots / fools (stupid), dick (male genitalia), tampol (slap), son of a bitch (bastard (slap) brash), and tonjok (hit). It was concluded that online games make many children absorb abusive or negative language so that the language behavior becomes bad. It is recommended to parents, teachers and policy makers not to recommend children to play online games that are specifically violent and have a verbal interaction menu.